2006
DOI: 10.1007/s11069-005-8604-6
|View full text |Cite
|
Sign up to set email alerts
|

People at Risk of Flooding: Why Some Residents Take Precautionary Action While Others Do Not

Abstract: Self-protective behavior by residents of flood-prone urban areas can reduce monetary flood damage by 80%, and reduce the need for public risk management. But, research on the determinants of private households' prevention of damage by natural hazards is rare, especially in Germany. To answer the question of why some people take precautionary action while others do not, a socio-psychological model based on Protection Motivation Theory (PMT) is developed, explaining private precautionary damage prevention by res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
1,043
12
11

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,073 publications
(1,199 citation statements)
references
References 17 publications
59
1,043
12
11
Order By: Relevance
“…In line with other studies (Grothmann and Reusswig 2006, Zaalberg et al 2009, Bubeck et al 2013, Osberghaus 2015, socio-economic variables explain relatively little of the data. Here, we only find that ownership positively influences the uptake of insurance (D2-D5) which is not surprising given the owners financial responsibility.…”
Section: Social Environment Previous Flood Experience Socio-economisupporting
confidence: 90%
See 3 more Smart Citations
“…In line with other studies (Grothmann and Reusswig 2006, Zaalberg et al 2009, Bubeck et al 2013, Osberghaus 2015, socio-economic variables explain relatively little of the data. Here, we only find that ownership positively influences the uptake of insurance (D2-D5) which is not surprising given the owners financial responsibility.…”
Section: Social Environment Previous Flood Experience Socio-economisupporting
confidence: 90%
“…Several empirical studies support the applicability of PMT to flooding: Grothmann and Reusswig (2006) applied PMT to flood adaptation behaviour of private households in Germany showing a good fit in contrast to socio-economic variables. Bubeck et al (2013) showed that coping appraisal is an important variable in terms of precautionary behaviour among flood-prone households along the river Rhine.…”
Section: Protection Motivation Theory and Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, older respondents (more than 65 years old), living in rural areas of Tanga region were more likely to perceive temperature Our result on age of respondents and perceived climate change is consistent with several studies. Age has been frequently associated with climate risk perception (see Grothmann and Reusswig 2006;Lindell and Hwang 2008;Kellens et al 2011). Similarly, several researchers highlight the role of education in shaping perceived climate risks (see Residual Plots for Rainfall in Mwanza Figure 18.…”
Section: Multinomial Logistic Regressionmentioning
confidence: 98%